Expanding airport capacity under constraints in large urban areas: The German experience - Hans-Martin Niemeier (Organisation for Economic Co-operation and Development (OECD), International Transport Forum, 2013)
Expanding airports is a topic which can easily make it to the first page of the national press. But this is highly unlikely as 'bad news' is 'good news' and most often failures and scandals make it to the front page. Berlin airport or the on-going failure to open up a nearly-complete new airport has been the front runner in this regard and gained so much international attention that the association of engineers fears that the world wide renowned reputation of German engineering might be seriously damaged.
Keywords: 330